Analysis of Product Diversity, Perceived Value, and Product Quality on Skintific Purchasing Decisions; Influencer Endorsement as a Moderating Variable - Selfiana, Ifa Sefti; Sukaesih, Imas; Utami, Wanda Yulia (Civiliza Publishing, Indonesia., 2025)
The development of the cosmetics industry in Indonesia, particularly in the skincare sector, has experienced significant growth. The purpose of this study was to examine how product diversity, perceived value, and product quality influence perceived value for Skintific in Tangerang, with influencer endorsement as a moderating variable. This study used a quantitative approach with a causal associative method. Data were collected through questionnaires from 180 Skinacre Skintific users and analyzed using SmartPLS 3 software to test the relationship between variables and their moderating effects. The results showed that all four variables had a positive and significant effect on purchase decisions. Influencer endorsement significantly moderated the relationship between the three variables and purchase decisions. This study addresses a gap in the literature by integrating four key variables that are typically studied separately and positioning influencer endorsement as a moderating variable in a model that has not been widely integrated.